PBL-Based Science Learning on Living Things Interaction in Junior High School - Hariyatmi, H; Tisniasari, Hidayatus Sholihah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
To obtain high learning outcomes, a teacher is required to teach students to use the right learning model. This study aims to analyze the effect of Problem Based Learning on the interaction of living things with their environment on learning outcomes in junior high schools. Experimental research with pretest posttest nonequivalent control group design. The object of this study is the results of student learning on the cognitive, affective, and psychomotor aspects. The sample used was two classes of students, as an experimental class and a control class and each of 28 students. Data collection techniques used were pretest-posttest, observation, and documentation. The research data were analyzed using the Independent Sample T-Test and the N-Gain test. The results showed that the average learning outcomes in the experimental class were higher than the average learning outcomes in the control class (N-gain 76>36.54); on Affective (73.21> 64.73) and Psychomotor (77.68> 65.62) aspects. Then analyzed using the Independent sample T-test. Based on the analysis of research results and discussion, it can be concluded that Problem Based Learning learning in the interaction of living things with their environment has an effective effect on junior high school student learning outcomes.